Thomas Kyd a dramatist restored - Vickers, Brian 1937- (Princeton University Press, 2024)
A groundbreaking new account of the author of The Spanish Tragedy that establishes him as a major Elizabethan dramatistThomas Kyd (1558-1594) was a highly regarded dramatist and the author of The Spanish Tragedy, the first revenge tragedy and the most influential Elizabethan play. In this first full study of his life and works, Brian Vickers discusses Kyd's accepted canon as well as three additional plays Vickers has newly identified as having been written by Kyd-exciting discoveries that establish him as a major dramatist.Thomas Dekker, a fellow Elizabethan dramatist, referred to industrious Kyd, which suggests a greater output than the three plays traditionally attributed to him-The Spanish Tragedy, Soliman and Perseda, and Cornelia. Kyd worked between 1585 and 1594, when the plague led to the anonymous publication of many plays because of the breakup of several London theatre companies. Researching this corpus, Vickers has identified Kyd's authorship of three more plays: Arden of Faversham, the first domestic tragedy, King Leir and his three daughters, a tragicomedy that provided Shakespeare with his main source, and Fair Em, a love comedy. These attributions are based on two forms of evidence: unique similarities of plot between Kyd's acknowledged and newly attributed plays and many unique phrases shared by all six plays as identified by modern software.Discussing all the plays in detail and placing them in biographical and historical context, Thomas Kyd offers a major reassessment of an underappreciated Elizabethan playwright